1976
DOI: 10.1002/art.1780190605
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of neoplasia in systemic lupus erythematosus and rheumatoid arthritis

Abstract: A patient population admitted to the hospital for either SLE or RA was surveyed for the subsequent development of neoplasms. The frequency of neoplasm in SLE patients appeared to be exaggerated, whereas the frequency of subsequent neoplasm in rheumatoid patients was unexpectedly low. A paucity of nephritis in the SLE group was noted. Further reports are encouraged so that the magnitude of the risk of malignancy developing with immunosuppressive therapy can be more precisely ascertained.Laboratory abnormalities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(48 citation statements)
references
References 12 publications
(3 reference statements)
1
45
1
1
Order By: Relevance
“…Furthermore, the risk for cancer was significantly lower compared with RA and SSc patients followed prospectively. Previous studies (1)(2)(3)(4)(5)(6) have shown the frequency of cancer in SLE patients to be between 2.5% and 7.3%. However, the data from most of those studies are difficult to interpret because of the small number of SLE patients or because of the lack of a suitable control population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the risk for cancer was significantly lower compared with RA and SSc patients followed prospectively. Previous studies (1)(2)(3)(4)(5)(6) have shown the frequency of cancer in SLE patients to be between 2.5% and 7.3%. However, the data from most of those studies are difficult to interpret because of the small number of SLE patients or because of the lack of a suitable control population.…”
Section: Discussionmentioning
confidence: 99%
“…A number of case reports have indicated a possible relationship between SLE and non-Hodgkin's lymphoma (NHL), Hodgkin's disease, and leukemia, as well as solid tumors (4)(5)(6)(7)(8). However, whether malignant neoplasms occur more commonly in patients with SLE compared with the general population is unclear.…”
mentioning
confidence: 99%
“…The first question, and the point on which published research has focused thus far, is whether the estimated malignancy risk for lupus patients is actually increased compared to the general population. The earliest clinical evidence of an association of cancer with systemic lupus erythematosus came from case and case series reports (12)(13)(14)(15). Since then, cohort studies (16)(17)(18)(19)(20)(21)(22) have produced sorne evidence of increased cancer risk in systemic lupus erythematosus patients, although the conclusions have not been uniform (23)(24)(25).…”
Section: Il Is Cancer Risk Increased In Systemic Lupus Erythematosus?mentioning
confidence: 99%
“…The malignancies seen did not differ in type from those occurring in the control group. Another review of 70 patients with SLE reported an 1 I .4% incidence of malignancy (3). Three-quarters of these patients had been treated with immunosuppressive agents.…”
Section: To the Editormentioning
confidence: 99%
“…Lymphoid neoplasms and multiple myeloma have been reported in patients with rheumatoid arthritis; however we do not know if the incidence of these neoplasms is actually increased in this population (2,3). Neoplasms and particularly carcinomas are apparently more frequent in patients with systemic lupus erythematosus (3). There is an increased frequency of lymphoid neoplasms in patients with Sjogren's syndrome (4).…”
Section: To the Editormentioning
confidence: 99%